The influence of slope on the identification of urban centralities: a case study in the municipality of Barra do Piraí, State of Rio de Janeiro, Brazil - Fontoura Júnior, Caio Flávio Martinez [UNESP]; Pugliesi, Edmur Azevedo [UNESP]; Tachibana, Vilma Mayumi [UNESP] (FapUNIFESP (SciELO), 2023)
This work considers the terrain slope factor as well as census dataset with variables related to socioeconomic and demographic characteristics, sanitation, water supply, garbage collection, and electricity in identifying centralities, or new urban centers in the municipality of Barra do Piraí, located in the State of Rio de Janeiro, Brazil, as a case study. The morphological approach was used with a Principal Components analysis and spatial analysis involving Global Moran Index, Local Indicator of Spatial Association – LISA, and Kernel Density Estimator. Among the variables considered in the study, results indicated that the slope was a preponderant factor in identifying the centralities in the study area and that it limits the urban expansion both in the municipality and in some existing districts.
Keywords: Kernel Density Estimator; Morphological Approach; Polycentrism; Principal Component Analysis; Spatial Autocorrelation